Ex vivo evaluation of the retention of procera® zirconia-yttria systems with different cements - Mejía-Bravo, Richard Milton; Caparroso-Pérez, Carlos Bernardo; Ruiz-Restrepo, Xiomara Cristina; Espitia-Mesa, José Fernando; Moreno-Castillo, Yenny Alexandra; Montoya-Sepúlveda, Andrés Felipe (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: since the specialized literature does not report reliable protocols for cementing zirconia-yttria restorations, the purpose of this study was to perform an ex vivo assessment of the retention by frictional strength of Procera® zirconia-yttria systems cemented with four materials: Ketac Cem (3M) ESPE), Multilink Automix (Ivoclar Vivadent), Panavia F 2.0 (Kuraray), and RelyX U100 (3M ESPE) on natural teeth. Methods: We gathered 40 recently extracted third molars, which were disinfected with 0.5% NaOCl and stored in saline solution, embedded in acrylic resin, and cut at a 10° convergence angle per wall with an axial carving of 1.5 mm in depth and 4 mm in height. Impressions were taken with Aquasil Ultra® Dentsply and cast with type IV plaster, obtaining 40 Procera AllZircon (Nobel Biocare) structures. 10 samples per material were cemented and thermocycled x 5,000 cycles of 15 s. They were then tractioned with a universal testing machine and failure types at the different interfaces were analyzed. One-way multiple-range ANOVA statistical analysis was performed. Results: average retention values in Newtons were 440 N for Ketac Cem, 698 N for Multilink Automix, 686 N for Panavia F 2.0, and 551 N for RelyX U100. Dentin adhesion failure occurred in 53.8% of cases, followed by mixed failure, with 12.82%. Conclusions: resinous cements with acid phosphate monomers reported higher retention values in comparison with conventional acid-base cements. Adherence to dentin and cement handling can affect the final result.